2019
DOI: 10.1152/ajpendo.00511.2018
|View full text |Cite
|
Sign up to set email alerts
|

Antiatherogenic effects of liraglutide in hyperglycemic apolipoprotein E-null mice via AMP-activated protein kinase-independent mechanisms

Abstract: Glucagon-like peptide-1 receptor agonists (GLP-1RAs) exert potent glucose-lowering effects without increasing risks for hypoglycemia and weight gain. Preclinical studies have demonstrated direct antiatherogenic effects of GLP-1RAs in normoglycemic animal models; however, the underlying mechanisms in hyperglycemic conditions have not been fully clarified. Here we aimed to elucidate the role of AMP-activated protein kinase (AMPK) in antiatherogenic effects of GLP-1RAs in hyperglycemic mice. Streptozotocin-induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 53 publications
2
33
0
Order By: Relevance
“…Both GIP and GLP-1 have been reported to exert direct effects on the cardiovascular system in addition to pancreatic beta cells [12,16]. Indeed, a number of preclinical studies, including ours, have shown the cardiovascular protective effects of native incretins and incretin-based agents partly in a glucose-lowering independent manner [17][18][19][20][21][22][23][24][25][26][27][28], whose observations were consistent with the recent cardiovascular outcome trials demonstrating that GLP-1RAs significantly reduced the cardiovascular and renal events in high-risk type 2 diabetic patients compared with placebo [29][30][31][32][33]. Furthermore, DPP-4 inhibitors have also been shown to improve surrogate markers of atherosclerotic CVD in several clinical trials [34][35][36], although their effects on CV hard events were neutral in various cardiovascular outcome trials [37][38][39][40][41].…”
Section: Introductionmentioning
confidence: 84%
“…Both GIP and GLP-1 have been reported to exert direct effects on the cardiovascular system in addition to pancreatic beta cells [12,16]. Indeed, a number of preclinical studies, including ours, have shown the cardiovascular protective effects of native incretins and incretin-based agents partly in a glucose-lowering independent manner [17][18][19][20][21][22][23][24][25][26][27][28], whose observations were consistent with the recent cardiovascular outcome trials demonstrating that GLP-1RAs significantly reduced the cardiovascular and renal events in high-risk type 2 diabetic patients compared with placebo [29][30][31][32][33]. Furthermore, DPP-4 inhibitors have also been shown to improve surrogate markers of atherosclerotic CVD in several clinical trials [34][35][36], although their effects on CV hard events were neutral in various cardiovascular outcome trials [37][38][39][40][41].…”
Section: Introductionmentioning
confidence: 84%
“…Multiple experimental studies have demonstrated that GLP-1 agonist treatment has anti-inflammatory effects on endothelial cells and monocytes through inhibition of inflammatory cascades involving vascular cell adhesion molecules and intracellular adhesion molecules [35][36][37]. In addition, a recent clinical study suggest that LIRA treatment decreases endoplasmic reticulum stress in endothelial cells and restores insulin-mediated endothelial NO production in patients with T2DM [38].…”
Section: Discussionmentioning
confidence: 99%
“…1 Glucagon was continuously infused to mice with osmotic pumps implanted in the dorsal subcutaneous tissue (Alzet minipump 1002; Cupertino, CA, USA). 10 The pumps were replaced every 14 days to avoid glucagon degradation. After 4 weeks of treatment with vehicle or glucagon, mice were euthanized by overdose of isoflurane, and blood and vascular samples were collected for biochemical, histopathological, and reverse-transcription polymerase chain reaction (RT-PCR) analyses.…”
Section: Animal Experimentsmentioning
confidence: 99%
“…Systolic blood pressure and pulse rates were measured using the non-invasive tail-cuff method as previously described. 10…”
Section: Measurement Of Plasma Levels and Blood Pressurementioning
confidence: 99%
See 1 more Smart Citation